Late Cretaceous granitoids of the Sikhote–Alin orogenic belt, southeastern Russia: implications for the Mesozoic geodynamic history of the eastern Asian continental margin. Issue 4 (2022) - Kemkin, Igor V.; Grebennikov, Andrei V.; Ma, Xing-Hua; Sun, Ke-Ke
No abstract available